2003
DOI: 10.1007/s10311-002-0007-2
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and Fenton's reagent oxidation of wastewater

Abstract: We compared two H 2 O 2 oxidation methods for the treatment of industrial wastewater: oxidation using Fenton's reagent [H 2 O 2 /Fe(II)] and microwave irradiation. Both methods were applied to the treatment of synthetic phenol solutions (100 mg L −1 ) and of an industrial effluent containing a mixture of ionic and non-ionic surfactants at high load (20 g L −1 of COD). The effects of initial pH, initial H 2 O 2 concentration, Fenton catalyst amount and irradiation time were assessed. According to the oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 10 publications
2
45
0
16
Order By: Relevance
“…Examples of 2 Advances in Environmental Chemistry AOPs include the use of hydrogen peroxide with ultraviolet light (H 2 O 2 /UV) to treat hazardous compounds [7], Fenton and photo-Fenton reagent (H 2 O 2 /Fe 2+ ) [8][9][10], semiconductor photocatalysis [11], and the sonolysis process using ultrasonic irradiation [12]. Among various AOPs, the Fenton reagent is one of the most effective methods for treating various industrial effluents including wastewater [13,14] and oily wastewater [15]. Previous work by the authors has involved the application of Fenton and the photo-Fenton reagents for the treatment of water polluted with diesel oil emulsion [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of 2 Advances in Environmental Chemistry AOPs include the use of hydrogen peroxide with ultraviolet light (H 2 O 2 /UV) to treat hazardous compounds [7], Fenton and photo-Fenton reagent (H 2 O 2 /Fe 2+ ) [8][9][10], semiconductor photocatalysis [11], and the sonolysis process using ultrasonic irradiation [12]. Among various AOPs, the Fenton reagent is one of the most effective methods for treating various industrial effluents including wastewater [13,14] and oily wastewater [15]. Previous work by the authors has involved the application of Fenton and the photo-Fenton reagents for the treatment of water polluted with diesel oil emulsion [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…Electro-magnetic vibration of microwave enhances the hydrolysis and also increases the temperature within a short time that helps to reduce ammonia. Sanz et al (2003) stated that microwave heating was much higher than that of ordinary heating at the same conditions which enhance the oxidation and rate of reaction. Microwave irradiation reduced the heating time by its molecular vibration and dissociated the complex molecule into simpler form within a short time.…”
Section: ⅲ Results and Discussionmentioning
confidence: 99%
“…High temperature with vibration also could induce the dissolution. Sanz et al (2003) showed that microwave irradiation dissociates the hydrogen peroxide and generates hydroxyl radicals due to the excitation of the molecule to high vibrational and rotational energy levels. Break down of MAP crystals occurred due to this high vibrational and rotational energy.…”
Section: ⅲ Results and Discussionmentioning
confidence: 99%
“…These processes involve the generation of highly free radicals, mainly hydroxyl radical (HO • ) The application of AOP`s in wastewater treatment leads to the degradation of the pollutant rather than transferring it to another phase, making the relevant technologies effective in the removal of organic pollutants in solution. In recent years, one of the main objectives of these processes mainly with highly polluted effluents has been not to mineralise the pollutant totally (AOP`s for complete mineralization are very expensive), but to improve the biodegradability for a possible coupling of the AOP`s with a conventional biological treatment process [Sanz et al 2003, Muñoz et al 2005]. …”
Section: Introductionmentioning
confidence: 99%